Chiral (VO)-O-IV-Sal-Indanol complex over modified SBA-15: an efficient, reusable enantioselective catalyst for asymmetric sulfoxidation reaction - Lazar, Anish; Sharma, Priti; Singh, A. P. (Microporous and Mesoporous Materials, 2013)
A reusable, mesoporous, heterogeneous vanadium complex, (VO)-O-IV-Sal-Ind-SBA-15 has been synthesized first time from (1R,2S)-(+)-Cis-1-amino-2-indanol for enantioselective sulfoxidation reaction. The physico-chemical properties of the functionalized catalyst were analyzed by a series of characterization techniques like XRD, N-2 sorption measurement isotherm, TEM, FT-IR, XPS, EPR, DRS UV-Visible, ICP-OES and solid & liquid state C-13, Si-29 and V-51 NMR spectroscopy. Powder X-ray diffraction patterns, TEM and N-2 physisorption analysis confirmed the retention of mesoporous structure after various modifications. Solid-state NMR (C-13 CP-MAS NMR, Si-29 MAS NMR) and FT-IR analysis certified the integrity of organo-catalyst residing inside the pore channels of the mesoporous support. Further, XPS, EPR, V-51 NMR and DRS UV-Visible analyses help to find out the oxidation state and coordination environment of vanadium in (VO)-O-IV-Sal-Ind-SBA-15. Catalytic evaluation in asymmetric sulfoxidation reaction of sulfides indicated that VOIV-Sal-Ind-SBA-15 exhibited higher catalytic activity, stability, reusability and comparable enantioselectivity than SBA-15, PrNH2-SBA-15, neat (VO)-O-IV-Sal-Indanol complex and without catalyst. The effect of different catalysts, temperature, solvents and substrates on sulfoxidation reaction were examined in order to optimize the conversion and enantioselectivity of thioanisoles to sulfoxides. Crown Copyright (C) 2012 Published by Elsevier Inc. All rights reserved.
Keywords: (1R; 2S)-(+)-Cis-1-amino-2-indanol; Asymmetric sulfoxidation; Heterogeneous vanadium complex; Mesoporous; Thioanisole

Clay encapsulated Cu(OH)(x) promoted homocoupling of arylboronic acids: an efficient and eco-friendly protocol - Dar, Bashir Ahmad; Singh, Snehil; Pandey, Nalini; Singh, A. P.; Sharma, Priti; Lazar, Anish; Sharma, Meena; Vishwakarma, Ram A.; Singh, Baldev (Applied Catalysis A-General, 2014)
Cu(OH)(x) has been encapsulated over montmorillonite-KSF by simple ologomeric deposition strategy. The resulting catalyst has been employed for selective homocoupling of arylboronic acids under ambient conditions without requirement of any ligand or base. This catalyst is easy to recover and shows excellent reusability without losing its activity. Techniques like XRD, SEM, TPR, IR, BET surface area measurement and XPS were used to characterize the catalyst. The present method promises for the simple and clean homocoupling of arylboronic acids. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Biaryls; clay; Copper; Heterogenous catalyst; Homocoupling

Covalently anchored 2,4,6-triallyloxy-1,3,5-triazine Pd(II) complex over a modified surface of SBA-15: catalytic application in hydrogenation reaction - Sharma, Priti; Singh, A. P. (RSC Advances, 2014)
Highly efficient and reusable SBA-15-TAT-Pd(II) has been synthesized by anchoring a 2,4,6-triallyloxy-1,3,5-triazine (TAT) complex over the organo-functionalized surface of SBA-15. The physiochemical properties of the organo-functionalized catalyst were analyzed by elemental analysis, ICP-OES, XRD, N-2 sorption measurement isotherm, TGA & DTA, solid state C-13, Si-29 NMR spectra, FT-IR, XPS, DRS UV-visible, SEM and TEM. XRD & N-2 sorption were analyzed to find out the textural properties of the synthesized catalyst and confirm that an ordered mesoporous channel structure was retained even after the multistep synthetic procedures. The electronic environment and oxidation state of Pd in SBA-15-TAT-Pd(II) were monitored by XPS and DRS UV-visible techniques. The catalytic activity of the synthesized catalyst SBA-15-TAT-Pd(II) was screened for hydrogenation reactions and shows higher catalytic activity with good turnover numbers (TON) under optimized experimental conditions with maximum conversion (> 99%) and selectivity (100%). The anchored solid catalyst can be recycled efficiently and reused upto five times without major loss in reactivity.

Carbon-carbon bond forming reactions: application of covalently anchored 2,4,6-triallyloxy-1,3,5-triazine (TAT) Pd(II) complex over modified surface of SBA-15 to Heck, Suzuki, Sonogashira and Hiyama cross coupling reactions - Singh, Chandani; Jawade, Kiran; Sharma, Priti; Singh, Anand P.; Kumar, Pradeep (Catalysis Communications, 2015)
A highly active SBA-15-TAT-Pd(II) catalyst was synthesized from organofunctionalized SBA-15 and 2,4,6-triallyloxy-1,3,5-triazine. The catalyst was employed in carrying out Heck, ``copper-free'' Sonogashira, Suzuki and Hiyama cross coupling reactions. Under the optimized conditions the catalyst displays excellent catalytic activity in delivering the desired products in good to excellent yields. The catalytic system exhibited superior activity regarding the time taken for the completion of reaction, isolation, Pd loading (0.62 mmol%) and yields of products as compared to the earlier reported heterogeneous SBA-15 anchored Pd catalysts. The catalyst could be recycled and reused for five times without any appreciable loss of catalytic activity. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Heck; Hiyama; SBA-15-TAT-Pd(II) catalyst; Sonogashira; Suzuki